2006
DOI: 10.1016/j.cplett.2006.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Rotational energy transfer in H2+H2

Abstract: Quantum-mechanical close-coupling calculations for state-to-state cross sections and thermal rates are reported for H2+H2 collisions. Two recently developed potential energy surfaces (PES) for the H2−H2 system are applied, namely, the global potential surface from the work of A.I. Boothroyd, P.G. Martin, W.J. Keogh, M.J. Peterson, J. Chem. Phys., 116 (2002) 666, and a restricted, model surface from the works of P. Diep, J.K. Johnson, J. Chem. Phys., 113 (2000) 3480; ibid. 112, 4465. The low temperature limit i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
(26 reference statements)
1
17
0
Order By: Relevance
“…12, 13 and in. 34 Therefore in this paper a new attempt has been undertaken to carry out alternative computational methods for HD+H 2 collision. In case of the BMKP and DJ PESs the necessary steps for each potential have been described in Secs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12, 13 and in. 34 Therefore in this paper a new attempt has been undertaken to carry out alternative computational methods for HD+H 2 collision. In case of the BMKP and DJ PESs the necessary steps for each potential have been described in Secs.…”
Section: Discussionmentioning
confidence: 99%
“…These PESs have been used in several different calculations. [32][33][34][35][36] However, in our previous works 12,34 we found that in the case of low energy H 2 +H 2 collision these PESs provide different results for some specific state-resolved cross sections. The difference may be up to an order of magnitude.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[39] it was shown that for a specific excitation rotational transition in the H 2 + H 2 inelastic scattering, for example, in H 2 (0) + H 2 (0) → H 2 (0) + H 2 (2), the BMKP PES provides an incorrect cross section when compared to the DJ potential. The comparison was also carried out with available experimental data [40].…”
Section: A Comparison Between Hd + Hd and H 2 + H 2 State-selected Imentioning
confidence: 99%